Systematic studies on Philippine shallow-water scleractinians II. Suborder Faviida - Nemenzo, Francisco 1935- (Quezon City, Philippines Natural and Applied Science Bulletin, 1959)
Natural and Applied Science Bulletincontents: II. Suborder Faviida (Montipora and Acropora). part 1 text, part 2 plates
Keywords: Scleractinian--shallow water; Astrocoeniida; Corals